A Survey on Criminal Identification using Multi Biometric Traits in Image Processing - Ganga Eswari, M; Dhanalakshmi, S; Karthik, S (International Journal of Computer Sciences and Engineering, 2025)
In recent years image processing gained the attention of many researches for criminal identification, medical science and Meteorology. This paper discussed about multi biometrics traits such as Face recognition, finger knuckle, RPPVSM, finger print, and vein pattern. Proposed work in this paper RPPVSM fusion with Vein pattern and finger knuckle for criminal identification. RPPVSM are different from birthmarks since birthmarks are congenital but RPPVSM can be congenital or acquired. The two main sections in RPPVSM i.e.) detection, matching. Then vein pattern is impossible for duplicate evidence. finger Knuckle biometrics is one of such promising modalities. Texture pattern produced by the finger knuckle bending is extremely unique and makes the surface a distinctive biometric identifier.